The Impact Of The Size Of SME Financing On The Profitability Indicators Of Commercial Banks (An Applied Study On A Sample Of Syrian Private Commercial Banks) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study aimed at showing the impact of the size of small and medium-sized companies financing on profitability indicators for Syrian private commercial banks The study was conducted for the period (2011 - 2018), where the researcher measured the size of the portfolio of small and medium loans (net medium and small loans / total loans) (as an independent variable), Bank profitability (as a dependent variable) (rate of return on assets, rate of return on equity, earnings per share). The study used the deductive approach in the research as a whole, and then the survey search design was used on a sample of private commercial banks in Syria. As for the method of data collection, the secondary data method was used by referring to the annual reports and official statistics of commercial banks, and the statistical study was carried out During the use of the SPSS statistical program. The results of the study showed that there is no impact of the volume of financing small and medium projects on the profitability indicators individually for the Syrian private commercial banks. هدفت هذه الدراسة إلى بيان أثر حجم تمويل الشركات الصغيرة والمتوسطة على مؤشرات الربحية للمصارف التجارية الخاصة السورية أجريت الدراسة للفترة (2011 –2018)، حيث قامت الباحثة بقياس حجم محفظة القروض الصغيرة والمتوسطة ( صافي القروض المتوسطة والصغيرة/ إجمالي القروض) (كمتغير مستقل)، ربحية المصرف (كمتغير تابع) ( معدل العائد على الأصول، معدل العائد على حقوق الملكية، ربحية السهم الواحد). استخدمت الدراسة المقاربة الاستنباطية في البحث ككل، ومن ثم تم استخدام تصميم البحث المسحي على عينة من المصارف التجارية الخاصة في سورية، أما بالنسبة لطريقة جمع البيانات تم استخدام البيانات الثانوية من خلال الرجوع إلى التقارير السنوية والإحصاءات الرسمية الخاصة بالمصارف التجارية، وتمت الدراسة الإحصائية من خلال استخدام البرنامج الإحصائي SPSS . اظهرت نتائج الدراسة عدم وجود أثر لحجم تمويل المشروعات الصغيرة والمتوسطة على مؤشرات الربحية بشكل منفرد للمصارف التجارية السورية الخاصة.